THE TASKS OF THE CHURCH AND THE STATE IN THE SERVICE OF MAN. SELECTED ISSUES - Mirosław Sitarz (Міжнародні відносини: теоретико-практичні аспекти, 2018)
The Church is a Divine-human reality to which belong all baptized people. The Church is a religious community with the main purpose and the supreme law to be souls salvation, according to the pribciple: Salus animarum suprema semper lex esse debet. The state is a natural community created by people to satisfy their simple needs. A man needs these two communities for his full development. The purpose of the article is to consider the question of the difference between the mission of the Church and the tasks of the State. The main methods of the research are comparison and analysis. The relationship between the Church and the state has always been delicate and complex. The system of relations between the Church – religious relations in the broadest sense – and the state should also be understood as a set of legal norms that operate at a certain time interval regulating the relationship between a religious and a political community. The Church-State system of relations is a certain set of doctrinal or ideological assumptions, as well as a way of their implementation in the political and social life of the Church in relation to the State and the State in relation to the Church. In the history of relations between the Church and the State, there existed various forms of their relationship, with the two main systems to be distinguished among: 1) the system of communication (religious and political monism, cesaropapism, papoesezrizm, jurisdictionalism), and 2) the system of the Church separation from the State (American model, French, German – referring to democratic states and the Soviet model – are associated with the totalitarian regime).